1979
DOI: 10.3109/02844317909013074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Lip Adhesion Procedure on the Alveolar Arch

Abstract: In a material of 89 wide clefts, we measured the effect of the lip adhesion on the width of the cleft, the deviation of the maxillary arch segments, and in bilateral clefts on the premaxillary protrusion. The width of the unilateral complete cleft diminished by two-thirds, on average, depending upon decreasing positive deviation of the major alveolar segment, while the minor segment did not react at all. In unilateral alveolar clefts the effect was in principle similar. In bilateral complete clefts the width o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…7 Studies have also shown that the protrusion of the premaxilla decreases by 8% to 23% and deviation decreases by 40% following lip adhesion surgery. 13 Other studies have demonstrated that lip adhesion surgery reduces the alveolar gap by 60% in patients with BCLP. 14 However, there is a risk that the soft tissue will break down due to the tension of the protruding premax-illa 15 frequently resulting in the need for additional revisional surgical procedures on the lip.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…7 Studies have also shown that the protrusion of the premaxilla decreases by 8% to 23% and deviation decreases by 40% following lip adhesion surgery. 13 Other studies have demonstrated that lip adhesion surgery reduces the alveolar gap by 60% in patients with BCLP. 14 However, there is a risk that the soft tissue will break down due to the tension of the protruding premax-illa 15 frequently resulting in the need for additional revisional surgical procedures on the lip.…”
Section: Discussionmentioning
confidence: 95%
“…The goal of lip adhesion is to retract the protruding premaxilla, bring the alveolar segments together, and minimize tension in the soft tissue before definitive lip surgery 7 . Studies have also shown that the protrusion of the premaxilla decreases by 8% to 23% and deviation decreases by 40% following lip adhesion surgery 13 . Other studies have demonstrated that lip adhesion surgery reduces the alveolar gap by 60% in patients with BCLP 14 .…”
Section: Discussionmentioning
confidence: 99%